Effects of Cognitive Behavioral Therapy for Insomnia on Sleep-Related Cognitions Among Patients With Stable Heart Failure. Issue 3 (4th May 2019) - Redeker, Nancy S.; Jeon, Sangchoon; Andrews, Laura; Cline, John; Mohsenin, Vahid; Jacoby, Daniel
ABSTRACT: Objective/Background : Cognitive behavioral therapy for insomnia (CBT-I) improves insomnia and fatigue among chronic heart failure (HF) patients, but the extent to which sleep-related cognitions explain CBT-I outcomes in these patients is unknown. We examined the effects of CBT-I on sleep-related cognitions, associations between changes in sleep-related cognitions and changes in sleep and symptoms after CBT-I, and the extent to which cognitions mediated the effects of CBT-I. Participants : Stable New York Heart Association Class II-III HF patients (total n  = 51; n  = 26 or 51.0% women; M age = 59.1 ± 15.1 years). Methods : HF patients were randomized in groups to group CBT-I ( n  = 30) or attention control (HF self-management education, n  = 21) and completed actigraphy, the Insomnia Severity Index, Pittsburgh Sleep Quality Index, Dysfunctional Beliefs and Attitudes about Sleep (DBAS) and Sleep Disturbance Questionnaires (SDQ), and self-reported fatigue, depression, anxiety, and sleepiness (baseline, immediately after treatment, six months). We used mixed-effects modeling, mediation analysis with a bootstrapping approach, and Pearson correlations. Results : There was a statistically significant group × mult time effect on DBAS. DBAS mediated the effects of CBT-I on insomnia severity and partially mediated CBT-I effects on fatigue. Improvements in dysfunctional cognitions were associated with improved sleep quality, insomnia severity, sleep latency and decreased fatigue, depression, and anxiety, with sustained effects at six months. Conclusions : Improvement in dysfunctional sleep-related cognitions is an important mechanism for CBT-I effects among HF patients who are especially vulnerable to poor sleep and high symptom burden.